ADA APA DENGAN SAP (AADS) AKRUAL? - Tresnawati, Eka Findi; Setiawan, Achdiar Redy (Jurnal Akuntansi Multiparadigma, 2013)
Abstract: What Happens with Acrual-Based SAP?. This article provides anoverview regarding SAP accrual-based and its problems. It compares information content of PP 24/2005âs cash toward accrual and PP 71/2010âs accrual-based toshow the urgency of accrual-based financial reporting requirements. The analysis borrows Abeysekaraâs accounting imperialism. Discussion also involves empirical evidence and evaluation of accrual-based implementation probability in Sumenep Regency. Findings show that accrual-based information is not an urgent need and tends to be difficult to be implemented. Reflecting the evidence in Sumenep, local governments are faced with the need of human resources, the question of the use-fulness of accrual information, and technical difficulties on implementation.Abstrak: Ada Apa Dengan SAP (AADS) Akrual?. Artikel ini memberikan gambaran mengenai SAP akrual dan problematikanya. Dimulai dengan telaah perbandingan konten informasi SAPPP 24/2005 berbasis cash toward accrual danÂ PP71/2010 berbasis akrual guna menunjukkan urgensi pemerintah daerahÂ (pemda) tentang kebutuhan pelaporan keuangan berbasis akrual. Alur pembahasan meminjam alur pikir imperialisme akuntansi Abeysekera. Pembahasan meliputi telaah empiris dan menunjukkan bahwa informasi laporan akrual sejatinya bukan merupakan kebutuhan urgen dan memiliki kecenderungan sulit diterapkan. Berkaca pada bukti di Sumenep, pemda dihadapkan pada kebutuhan sumber daya manusia, pertanyaan tentang kebermanfaatan informasi akrual dan kesulitan teknis pelaksanaannya.